Analysis of INIS, MSCI, INSPEC databases concerning the dynamics of publications on low-activated chromium alloys for use in the nuclear and fusion power engineering - Shepelev, A.G.; Kurilo, Yu.P.; Krivchenko, O.V.; Nemashkalo, O.N. (Вопросы атомной науки и техники, 2014)
The paper presents the results of scientometric analysis of data flows from the International Databases, over a
period since 1971 to 2011, on low-activated chromium alloys suitable for operation under extremely hard conditions
in nuclear and fusion reactors. A detailed analysis of three Databases makes it possible to obtain the data on temporal
trends of publications and on contributions to them from different countries, as well as, to define the type of publications
and their languages. It is shown that investigations and developments on low-activated chromium alloys are
of current importance. Обсуждаются результаты наукометрического анализа информационных потоков в Международных базах данных с 1971 по 2011 гг. по малоактивируемым сплавам хрома, которые применялись для крайне тяжелых условий работы ядерных и термоядерных реакторов. Подробный анализ трех указанных автоматизированных Баз данных дал возможность получить данные о временной динамике публикаций, а также о вкладе в них конкретных стран; определены типы публикаций и их языки. Показано, что исследования и разработки малоактивируемых сплавов хрома являются актуальными. Обговорюються результати наукометричного аналізу інформаційних потоків у Міжнародних базах даних
з 1971 по 2011 рр. по малоактивованим сплавам хрому, придатних для вкрай важких умов роботи ядерних і
термоядерних реакторів. Докладний аналіз трьох зазначених автоматизованих Баз даних дав можливість
отримати дані про динаміку публікацій в часі, а також про внесок у них конкретних країн; визначено типи
публікацій і їхні мови. Показано, що дослідження і розробки малоактивованих сплавів хрому є актуальними.